Science Across the World: Interview with Monica Tosi, Argentine Representative for SAW (Transcript Podcast) - Susan Hillyard (Universidad de La Sabana, 2010)
In this podcast, Susan Hillyard interviews Monica Tosi, the Argentine Representative for Science Across the World (SAW). Tosi explains the focus of SAW and how teachers can get involved. Comments are offered on benefits for teachers and students, as well as the status of CLIL in Argentina.